Durango apatite fission-track dating using length-based age corrections and neutron fluence measurements by natural thorium thin films and natural U-doped glasses calibrated through natural uranium thin films - Iunes, P. J.; Hadler, J. C.; Bigazzi, G.; Tello, C. A.; Guedes, S.; Paulo, SR (Elsevier B.V., 2002)
In this work, we present an approach for neutron fluence measurements based on natural thorium thin films and natural uranium-doped glasses calibrated through natural uranium thin films to be used for dating with the Fission-Track Method (FTM). This neutron dosimetry approach allows the employment of FTM even when dating is carried out using low neutron themalization facilities. Besides, it makes possible the determination of the Th/U ratio of the mineral to be dated. Durango apatite which is often employed in FTM as an age standard was analyzed. This apatite presented a fairly high Th/U ratio, 29.9 +/- 1.7. Th fissions were 18%, 12% and 10% of the total for irradiations where thermal to fast neutron flux ratios were 2.4, 4.4 and 5,2, respectively. These results show that Th fission must be considered for this apatite, when not well-thermalized irradiation facilities are used. The ratio between spontaneous and induced track length, L(S)/L(1), close to 0.89, indicates a certain amount of rejuvenation of the age of Durango apatite. Therefore, its apparent age should be corrected, the application of a technique based on track-length measurements produced a corrected age of 29.7 +/- 1.1 Ma, consistent with the independent reference age of this apatite (31.4 +/- 0.5 Ma). This result represents a support for viability of the neutron dosimetry approach studied in this work for FTM.(C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: uranium thin film; thorium thin film; neutron dosimetry; fission-track dating; Durango apatite